SELF EFFICACY, TOLERANCE FOR RISK DAN ENTREPRENEURIAL EDUCATION DALAM MENUMBUHKAN MINAT WIRAUSAHA MAHASISWA DI KOTA PONTIANAK - Irdhayanti, Efa; Ahmadi, Ahmadi; Mufrihah, Mazayatul (Universitas Prof. Dr. Hazairin SH, 2022)
The purpose of this study is to identify the effect of self-efficacy, tolerance for risk, and Entrepreneurship education in growing student entrepreneurial interest in Pontianak City. This study uses a causative type of research, namely the type of research with the characteristics of the problem in the form of a causal relationship between two or more variables. Sampling used purposive sampling method. Questionnaires were distributed to 200 respondents. The returned and usable questionnaires were 139 questionnaires. The results of the study are self-efficacy, tolerance for risk and Entrepreneurship education have a positive and significant effect on student entrepreneurial interest in Pontianak City. This research is expected to contribute to educators in formulating teaching materials and contributions to the government as input in making programs related for producing many young entrepreneurs.